Perbedaan Luaran Maternal dan Perinatal pada Preeklamsia Onset Dini dan Onset Lambat di RSUP Prof. Dr. R. D. Kandou Manado - Natan Arikalang; Erna Suparman; John J. E. Wantania (Universitas Sam Ratulangi, 2026)
Abstract: Timing of preeclampsia onset, early-onset (<34 weeks) and late-onset (≥34 weeks), is known to be associated with varying degrees of severity and pregnancy outcomes. This study aimed to determine the differences in maternal and perinatal outcomes between early-onset and late-onset preeclampsia at Prof. Dr. R. D. Kandou General Hospital Manado during years 2022–2024. This was an analytical and observational study with a cross-sectional approach. Data were collected retrospectively from medical records using a total sampling technique. Data were analyzed using the chi-square test or Fisher’s exact test. The results obtained 488 patients that met the inclusion criteria, consisting of 159 patients with early-onset preeclampsia and 329 patients with late-onset preeclampsia. Maternal outcomes such as eclampsia (13.2% vs 1.8%; p<0,001), HELLP syndrome (33.3% vs 4.9%; p<0.001), and maternal mortality (5.0% vs 0.9%; p=0.007) were significantly higher in the early-onset group. Meanwhile, pulmonary edema and placental abruption showed no significant difference. For perinatal outcomes, early-onset preeclampsia demonstrated a markedly higher rate of complications, including prematurity (91.8%), low birth weight (92.5%), neonatal asphyxia (58.5%), IUGR (34.0%), and perinatal mortality (54.7%), all with p<0.001 compared to the late-onset group. In conclusion, there are significant differences in maternal and perinatal outcomes between early-onset and late-onset preeclampsia at Prof. Dr. R. D. Kandou General Hospital Manado, with early-onset preeclampsia being associated with poorer maternal and perinatal outcomes. Keywords: preeclampsia; early-onset; late-onset; maternal outcomes; perinatal outcomes Abstrak: Waktu munculnya preeklamsia, yaitu onset dini (<34 minggu) dan onset lambat (≥34 minggu), diketahui berkaitan dengan variasi tingkat keparahan dan luaran kehamilan. Penelitian ini bertujuan untuk mengetahui perbedaan luaran maternal dan perinatal pada preeklamsia onset dini dan onset lambat di RSUP Prof. Dr. R. D. Kandou Manado periode 2022–2024. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Data dikumpulkan secara retrospektif melalui rekam medis menggunakan teknik total sampling Hasil penelitian mendapatkan 488 pasien yang memenuhi kriteria inklusi, terdiri dari 159 pasien dengan preeklamsia onset dini dan 329 pasien dengan onset lambat. Analisis statistik menggunakan uji chi-square atau Fisher’s Exact. Luaran maternal seperti eklampsia (13,2% vs 1,8%; p<0,001), sindrom HELLP (33,3% vs 4,9%; p<0,001), serta mortalitas maternal (5,0% vs 0,9%; p=0,007) secara bermakna lebih tinggi pada kelompok onset dini, sedangkan edema paru dan solusio plasenta tidak menunjukkan perbedaan bermakna. Pada luaran perinatal, onset dini memiliki proporsi komplikasi yang jauh lebih tinggi, mencakup prematuritas (91,8%), BBLR (92,5%), asfiksia neonatorum (58,5%), IUGR (34,0%), dan mortalitas perinatal (54,7%), seluruhnya dengan nilai p<0,001 dibanding onset lambat. Simpulan penelitian ini ialah terdapat perbedaan bermakna antara luaran maternal dan perinatal pada pasien preeklamsia onset dini dan onset lambat di RSUP Prof. Dr. R. D. Kandou Manado, dimana onset dini berkaitan dengan luaran maternal dan perinatal yang lebih buruk. Kata kunci: preeklamsia; onset dini; onset lambat; luaran maternal; luaran perinatal